Unlocking the future of swimming education: A breakthrough in pull buoy development as an innovative learning medium - Marhadi, Marhadi; Hazar, Fatih (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
The effectiveness of the learning process in swimming greatly depends on innovative learning media. This research aims to develop and produce a pull buoy as an effective swimming learning medium. This research uses the ADDIE model for Research and Development (R&D) research. The study was conducted at Tadulako University with the collaboration of swimming material experts, instructional design experts, and learning media experts. The research involved 40 students enrolled in swimming learning courses, and data were collected through observation and questionnaires. The assessment by learning design and learning media experts revealed that the developed Pull Buoy achieved high-quality learning standards. Furthermore, both small group and large group evaluations demonstrated feasibility and outstanding performance. The research offers valuable insights and recommendations for future researchers to refine and expand the Pull Buoy's development, suggesting customization of its colour combinations and sizes to suit different age groups of users and advocating for a larger pool of subjects to yield more comprehensive results and insights into the learning medium's impact.